2022
DOI: 10.1002/adma.202205698
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Electron Correlation at a 3d Ferromagnetic Surface

Abstract: Spin‐resolved momentum microscopy and theoretical calculations are combined beyond the one‐electron approximation to unveil the spin‐dependent electronic structure of the interface formed between iron (Fe) and an ordered oxygen (O) atomic layer, and an adsorbate‐induced enhancement of electronic correlations is found. It is demonstrated that this enhancement is responsible for a drastic narrowing of the Fe d‐bands close to the Fermi energy (EF) and a reduction of the exchange splitting, which is not accounted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Other authors have reported a strong Dzyaloshinskii-Moriya interaction [3] induced by the chemisorption of oxygen on a FM Ni layer at room temperature via spin-polarized low-energy electron microscopy (SPLEEM) [110]. Others authors have observed a change in the electron correlation on the FM catalyst surface due to the adsorption of O atoms [111]. Another interesting example is the work of M. Kurahashi and Y. Yamauchi on O 2 adsorption over an in-plane magnetized Ni(111) film carried out using spin-and alignment-resolved chemisorption techniques [112,113].…”
Section: Experimental Evidence On Magnetism-covalent Bonding Interpla...mentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors have reported a strong Dzyaloshinskii-Moriya interaction [3] induced by the chemisorption of oxygen on a FM Ni layer at room temperature via spin-polarized low-energy electron microscopy (SPLEEM) [110]. Others authors have observed a change in the electron correlation on the FM catalyst surface due to the adsorption of O atoms [111]. Another interesting example is the work of M. Kurahashi and Y. Yamauchi on O 2 adsorption over an in-plane magnetized Ni(111) film carried out using spin-and alignment-resolved chemisorption techniques [112,113].…”
Section: Experimental Evidence On Magnetism-covalent Bonding Interpla...mentioning
confidence: 99%
“…Another interesting example is the work of M. Kurahashi and Y. Yamauchi on O 2 adsorption over an in-plane magnetized Ni(111) film carried out using spin-and alignment-resolved chemisorption techniques [112,113]. Their results show that the sticking probability of O 2 over magnetized Ni (111) film is different with parallel and antiparallel spin orientations of the paramagnetic molecule, with respect to the majority of the spins' direction on the catalyst surface. The preferred O 2 spin orientation is the one antiparallel to the spin orientation of the FM catalyst.…”
Section: Experimental Evidence On Magnetism-covalent Bonding Interpla...mentioning
confidence: 99%
“…Even for metallic systems, it may be necessary to go beyond the one-electron picture, as suggested by the recent work of Janas et al, 28 in which the authors discuss how the adsorption of oxygen atoms on the surface of ferromagnetic iron leads to a While the above study reports that chemisorption affects band ferromagnetism by collapsing the exchange splitting close to the Fermi level, there are other studies that report the opposite behavior. In certain 3d transition metals, chemisorption may affect the Stoner criterion for the appearance of magnetism, where the interface between metallic thin films and C60 molecular layers modifies the states of metal in such a way that they can overcome the Stoner criterion, resulting in the emergence of ferromagnetic behavior at room temperature in nonferromagnetic materials.…”
Section: Down Spinmentioning
confidence: 99%
“…Even for metallic systems, it may be necessary to go beyond the one-electron picture, as suggested by the recent work of Janas et al., in which the authors discuss how the adsorption of oxygen atoms on the surface of ferromagnetic iron leads to a breakdown of the Stoner-like picture of band ferromagnetism. This is evidenced by the reduction of the exchange splitting, the narrowing and localization of hybrid Fe–O states, and the appearance of spin-polarized adsorbate-FM satellite features.…”
mentioning
confidence: 99%